AutoCAD2017 beginning and intermediate - Hamad, Munir (Mercury Learning, 2017)
Covering all of the 2D drafting concepts and including over 100 "mini-workshops" that complete small projects from concept through actual plotting, this book uses both metric and imperial units to illustrate the myriad drawing and editing tools for this popular application. --